Информационная модель управления технологическими комплексами непрерывного типа в классе организационно-технических систем - Прокопенко, Т.А.; Ладанюк, А.П. (Проблемы управления и информатики, 2014)
Розглянуто використання мультиагентного підходу при моделюванні управління технологічними комплексами (ТК) неперервного типу в класі організаційнотехнічних систем. Запропоновано формалізований опис агентів управління ТК в умовах невизначеності з застосуванням алгебри поведінки. The use of multiagent approach to control of the continuous type technological complexes in the class of organizational and technical systems is considered. The types of agents which model different objects of the system and environment are defined. The formalized description of agents of the technological complex control under uncertainty conditions with the use of behaviour algebra is presented.